2016
DOI: 10.1002/app.44522
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hydrophilic dimethyl 5‐sodium sulfoisophthalate/poly(ethylene terephthalate) nanofiber composite membranes for improving antifouling properties

Abstract: In this study, the effect of dimethyl 5-sodium sulfoisophthalate (SSI) nanoparticles (NPs) on the antifouling properties of poly(ethylene terephthalate) (PET) electrospun nanofiber membranes (ENMs) was investigated through the ultrafiltration of C. I. Basic Blue 3. 3 dye. To reveal the tortuous effect of this additive on the antifouling properties, scanning electron microscopy was used for the characterization of the ENM structure and the optimization of the SSI NP content. Then, some selected physical and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…38 Thereafter, Chegoonian et al showed that the viscosity of polyester solution gradually increases with rising DMSSIP concentration which in fact increases nanofiber diameter and reduces the membrane porosity. 29 Herein, one possible explanation for the contradictory effects of nanoparticles on the average nanofiber diameters appears to be the influence of the nanoparticles on the solution viscosity which was also investigated. Figure 4 shows the effects of the solution concentration and the mass ratio of the nanoparticles on the solution viscosity.…”
Section: Nanofibers Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…38 Thereafter, Chegoonian et al showed that the viscosity of polyester solution gradually increases with rising DMSSIP concentration which in fact increases nanofiber diameter and reduces the membrane porosity. 29 Herein, one possible explanation for the contradictory effects of nanoparticles on the average nanofiber diameters appears to be the influence of the nanoparticles on the solution viscosity which was also investigated. Figure 4 shows the effects of the solution concentration and the mass ratio of the nanoparticles on the solution viscosity.…”
Section: Nanofibers Morphologymentioning
confidence: 99%
“…Chegoonian et al found out the improved antifouling properties of polyester membranes when used with dimethyl 5-sodium sulfoisophthalate (DMSSIP). 29 More research and investigation are needed to be done about the wicking ability of polyester filaments that include DMSSIP in a core-sheath yarn. Poly(ethylene terephthalate) (PET) as one of the most durable and widely used polymers is resistant to most chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity index between various experiment results and the positive ideal solution is obtained by equations (10) to (14), as shown in Table 11.…”
Section: Multi-quality Optimization Analysismentioning
confidence: 99%